Projecting future utilization of medically assisted fertility treatments. (2nd January 2020) - Raymer, James; Guan, Qing; Norman, Robert J.; Ledger, William; Chambers, Georgina M.
Abstract : This study estimates the future utilization of medically assisted fertility treatments in Australia, focusing on assisted reproductive technologies (ARTs), intrauterine insemination (IUI), and ovulation induction. A multistate cohort component population projection model is used to determine future fertility rates from 2016 to 2026 by age and education level. These are combined with information on recent trends in use and success rates to indirectly estimate future age-specific probabilities of fertility treatment utilization. The number of ART cycles is expected to increase by 61 per cent between 2016 and 2026 if treatment success rates remain at 2015 levels, or by 34 per cent if recent improvements in ART success rates continue. The model also predicts that numbers of IUI cycles and ovulation induction cycles will decrease by 17 and 3 per cent, respectively. This research confirms the importance of including both technological improvements and socio-demographic changes when predicting future fertility treatment utilization.